Multistage tectono‐magmatic evolution of the central Urumieh–Dokhtar magmatic arc, south Ardestan, Iran: Insights from zircon geochronology and geochemistry. (2nd October 2018) - Babazadeh, Shahrouz; Ghorbani, Mohammad Reza; Cottle, John M.; Bröcker, Michael
Abstract : Combining high‐spatial resolution geochronology and geochemistry of zircon provides constraints on the geodynamic evolution of the Zagros orogen. This study underlines the significance of hitherto unknown magmatic/geological events in the central Urumieh–Dokhtar magmatic arc (UDMA) of Iran at ca. 35–22 and 10 Ma. Recently reported U–Pb zircon ages of 25–24 Ma for the granodioritic rocks from the south Ardestan area were interpreted to constrain the crystallization age. Newly determined U–Pb zircon ages of ca. 35 to 22 Ma from south Ardestan gabbroic to granitic rocks and related dikes indicate that the melt evolution continued from the Oligocene into Early Miocene time. In addition, a ca. 10 Ma U–Pb age for the zircons from a south Ardestan diorite provides evidence for a so far unknown, igneous episode. Representing the youngest magmatic stage recognized in the central part of the UDMA, the 10 Ma age is interpreted to document magmatic activity related to the Arabia–Eurasia collision, as recognized elsewhere in the Zagros orogen. South Ardestan zircons with geochemical signatures indicating continental affinity likely recrystallized in the course of a major event (asthenospheric mantle melt formation) that has affected crustal rocks. The significant lower LREEs of these zircons compared to hydrothermal zircons, moderate Th/U (>0.4), and high (Sm/La)N (>10) ratios associated with low [La] (<1 ppm) suggest that these crystals have an igneous origin and are not related to hydrothermal or metamorphic processes. These findings bear important implications for the geodynamic evolution of the Zagros orogen and support a model suggesting that magmatic activity still affected the UDMA in Late Miocene time.